2012
DOI: 10.2478/v10105-012-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Places that Matter: Place Attachment and Wellbeing of Older Antillean Migrants in the Netherlands

Abstract: It has been argued that attachment to place increases wellbeing in old age (Wiles et al., 2009). Feeling ‘in place’ can increase an older person's wellbeing. For older migrants it can be a challenge to live in-between cultures. The objective of the article is to explore how older Antillean migrants derive a sense of wellbeing from attachment to their everyday places. We do so by drawing on in-depth interviews and a photography project with Antilleans who live in a senior cohousing community in a city i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…Senior co-housing communities are still rather marginal options, although more common in the Netherlands, Denmark, and Sweden (Choi, 2004). Previous studies have shown that avoiding social isolation and finding a community of like-minded people are the most common reasons for moving to an agespecific housing type (Bernard et al, 2007(Bernard et al, , 2013Glass, 2009Glass, , 2013Glass & Vander Plaats, 2013;Lager et al, 2012;Stimson & McCrea, 2004). From the beginning, co-housing schemes were developed as a housing type that would alleviate the loneliness of older people by providing mutual support and social contacts (Choi, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Senior co-housing communities are still rather marginal options, although more common in the Netherlands, Denmark, and Sweden (Choi, 2004). Previous studies have shown that avoiding social isolation and finding a community of like-minded people are the most common reasons for moving to an agespecific housing type (Bernard et al, 2007(Bernard et al, , 2013Glass, 2009Glass, , 2013Glass & Vander Plaats, 2013;Lager et al, 2012;Stimson & McCrea, 2004). From the beginning, co-housing schemes were developed as a housing type that would alleviate the loneliness of older people by providing mutual support and social contacts (Choi, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Some new age-specific housing arrangements, such as retirement villages (Bernard, Bartlam, Sim, & Biggs, 2007), migrant retirement villages (Lager, van Hoven, & Meijering, 2012), continuing care retirement communities (Krout, Moen, Holmes, Oggins, & Bowen, 2002), and senior co-housing communities (Choi, 2004;Glass, 2009Glass, , 2013 of providing better support for individual lifestyles and residents' autonomy, social contacts, and chances to participate in the community. Senior co-housing communities are still rather marginal options, although more common in the Netherlands, Denmark, and Sweden (Choi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The place of residence in a multicultural country also emerged as an important factor among urban and rural residents in Western Australia (Anton & Lawrence, ), pointing to the residential neighborhood as an important migration variable in studying SOP. A similar study was conducted in a Dutch context, in which researchers examined people–place relationships in deprived neighborhoods among Dutch citizens (Lager, van Hoven, & Meijering, ; van der Graaf, ). Lager et al.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Lager et al. () suggest that the place of residence (e.g., in co‐housing communities) serves as a central setting of experience from which migrants explored their broader environment and formed new attachments in the community.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation